MECHANISMS OF TRANSACTION COST REDUCTION IN THE DIGITAL PLATFORM ENVIRONMENT - Nematjonova Risolatxon Dilshodbek qizi (TADQIQOTLAR, 2026)
Abstract This article examines the mechanisms for reducing transaction costs within the framework of the digital economy and platform ecosystems. Based on the institutional theories of Ronald Coase and Oliver Williamson, the optimization of information search, negotiation, and contracting costs under the influence of digital technologies (blockchain, artificial intelligence, smart contracts, asynchronous communication) is analyzed. The study mathematically and empirically highlights how digital platforms enhance market efficiency by displacing traditional intermediaries (disintermediation) and elevating the institution of trust to a new level.